The ADDIE Model As An Instrument for Designing HEMA-MAGZ (Healthy Motion Magazine) Media - Susindra, Yoswenita; Setyowati, Lisus; Satya, Malinda Capri Nurul; Sari, Dian Kartika; Suandana, Iwan Abdi (Indonesian Journal Publisher, 2025)
Clean and healthy living behavior (PHBS) in the work environment is an important aspect which contributes to employees welfare and organizational productivity. However, the implementation of PHBS often faces challenges such as a lack of understanding and awareness of the importance of PHBS in the workplace. This research aims to develop and implement HEMA-MAGZ (Healthy Motion Magazine) as an effective communication, information, and educational media in supporting the implementation of PHBS in the work environment of Tefa House in Health Promotion Major, Jember State Polytechnic. This research method uses the R&D (Research and Development) model to design IEC PHBS media in the Hema-Magz work environment using the ADDIE (Analyze, Design, Development, Implementation, and Evaluation). HEMA-MAGZ is designed as an interactive magazine which contains educational content regarding 10 PHBS indicators, namely (Using Personal Protective Equipment (PPE), regular exercise, not smoking, washing hands with soap in daily activity, tips for defecating and urinating in the bathroom, exterminate mosquito larvae, throwing away rubbish on the right trash bin, avoiding drugs, consuming clean and healthy food and drinks, and not spitting anywhere. The research results show that HEMA-MAGZ has succeeded increasing employees awareness and understanding of PHBS, which is reflected increasing healthy living behavior in the work environment. Furthermore, this magazine also received positive responses from employees who felt the contents are attractive and easy to understand. This research concludes if HEMA-MAGZ is an effective media in conveying information and education.